Shaving as a subscription : analysis of Portuguese male consumers interest on buying razors and blades by subscription - Martins, Pedro Maria Menezes da Silva (2019)
Men’s grooming market has been growing significantly, mostly because men are increasingly concerned about their appearance. This self-image consciousness made this market evolve and present today a large variety of products specifically designed for men. The old razors and blades category still represents a big slice of this market and continues being dominated by Gillette. However, new players have recently entered the shaving market with a subscription service that delivers razors and blades to consumers’ homes at a lower price. This concept has proven to be a huge success and revolutionized the US market. This study intends to explore the interest of Portuguese male consumers in this service, firstly by identifying the main advantages and disadvantages consumers may have, then their possible interest and the predictors of that interest, and finally by addressing their loyalty to the brands they use. For this purpose, past literature on this topic and related subjects were reviewed, 14 qualitative interviews were conducted, as well as an online survey with a sample of 110 participants. Findings showed that the main benefit for consumers was paying less, whereas the main drawbacks were the possibility of having the product damaged when delivered or delivered to the wrong address. The majority of respondents were interested in subscribing and their reaction to the concept and confidence about the product’s quality were key determinants. Additionally, results exhibited high levels of loyalty from shaving consumers. The final assessment is that these services have a good probability to succeed in Portugal.